STRATEGI BALAI PENJAMINAN MUTU PENDIDIKAN DALAM OPTIMALISASI PLATFORM MERDEKA MENGAJAR DI DAERAH ISTIMEWA YOGYAKARTA - Nur Ratih; Wendhie Prayitno; Missa Serriawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategies of the Educational Quality Assurance Agency (Balai Penjaminan Mutu Pendidikan/BPMP) of the Special Region of Yogyakarta (DIY) in optimizing the utilization of the Merdeka Mengajar Platform (PMM), as well as to identify its supporting factors, obstacles, and feature utilization. This research employed a qualitative method with a phenomenological approach, focusing on the experiences of BPMP DIY officials and staff. Data were collected through observation, in-depth interviews, and documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing, supported by triangulation techniques to ensure data validity. The findings indicate that BPMP DIY’s strategy is implemented through an operational approach that integrates PMM into direct assistance for the implementation of the Merdeka Curriculum (Implementasi Kurikulum Merdeka/IKM) and data-based management to determine priority target schools. The main supporting factors include strong institutional policies and the culture of teacher literacy in DIY, while the obstacles identified include the low digital literacy of senior teachers, administrative workloads, and the perception of PMM as an additional reporting burden. The most dominantly utilized PMM features are Teaching Modules, Inspirational Videos, and Independent Training. Overall, BPMP DIY’s strategic management plays a key role in transforming the use of the platform from merely an administrative obligation into a need for continuous professional development.